Cultural identity and beef festivals: toward a 'multiculturalism against caste'. Issue 3 (3rd July 2018) - Natrajan, Balmurli
Abstract : Beef festivals are a dramatic and visible form of protest against the Indian government's ban on beef. These festivals are framed popularly as an assertion of Dalit 'cultural rights' and identity, with beef represented as the cultural food of Dalits. While it is clear that the beef ban is a casteist ban based on a Brahmanical food hierarchy, this paper explores the limits of resisting casteism through the assertion of caste-based cultural rights and identities, or as an assertion of an individual right to food choice. It argues that such a politics of resisting casteism runs into problems of the culturalization of caste, and limits the kinds of radical Dalit subjects and actors who could emerge as liberatory political subjects. The paper calls for reframing beef festivals as 'antagonistic' moments that articulate the degradation of Dalit labor in the politics of beef, reassert Dalit identity as an anti-caste identity rather than a cultural caste identity, and herald a politics of 'multiculturalism against caste'.